"Miscuit cum eis" (s. 232,3): Agostinho e a arte do acompanhamento a partir de Lc 24,13-35 - D'Andrea, Bruno ca. ca. 21. Jh. (Mayéutica, 2023)
The article presents the main aspects of the art of accompaniment inspired by the augustinian exegesis of Lk 24:13-35, not without resorting, when necessary, to other relevant texts of the Bishop of Hippo. For this purpose, after a brief introduction which shows the actuality of the theme in the ecclesial sphere, it is briefly presented how Augustine interprets the life of the human being based on the metaphor of the journey and the pilgrimage, and how he conceives them to be a time and a path of harmonious growth. This serves as a framework to offer Augustinian orientations for the art of accompaniment based on his interpretation of Lk 24:13-35. It is shown that Augustine has been little explored as a relevant figure for the Christian tradition of accompaniment.